Eksplorasi Kebutuhan E-Modul Hypercontent Edukasi tentang Stunting - Erma Agustina; Tri Murwaningsih; Eka Budhi Santosa (Departement of Mathematics Education, 2023)
Stunting prevention is important for mothers so that their children grow up healthy and have a brighter future. Therefore, this research aims to identify and explore the need for an electronic module to provide understanding to residents about the dangers of stunting. This research is a type of qualitative research, the interview guide was used as an instrument to collect data in the form of responses from three Village Midwives who were selected using purposive sampling. The findings from this research show that residents do not have a real understanding of the dangers of stunting, so they do not know how to avoid it. On the other hand, midwives who understand how important it is to maintain children's nutrition at the age of 1000 HPK, stated the need for media that can accessed by residents, especially mothers, about health and maintaining balanced nutrition for their babies to avoid stunting. One of the relevant media to address this need is an e-module with hypercontent characteristics, where the material will be very rich and not limited by textual material. Therefore, understanding the importance of 1000 HPK as a first step in preventing stunting is deemed necessary to be distributed to residents through a digital tool or device.